Preliminary Smithsonian identification manual seabirds of the tropical Atlantic ocean - Watson, George Elder, 1931- (Washington, D.C. Smithsonian Instituttion, 1965)
Smithsonian identification manualPublication (Smithsonian Institution) ; 4680
Keywords: ocean; Atlantic Ocean; Sea birds--Identification.